A review of telecollaboration technologies with respect to closely coupled collaboration. (15th June 2007) - Wolff, Robin; Roberts, Dave J.; Steed, Anthony; Otto, Oliver
Many existing Computer-Supported Cooperative Work (CSCW) systems have two major deficiencies. Firstly, they support the situation of face-to-face meetings poorly. Secondly, many systems deal badly with data sets and workspaces. This paper outlines the requirements for a class of CSCW tools that would focus on supporting closely coupled collaborative activity around shared objects. These requirements include the ability to refer to a common model of the shared space through speech and gesture and for each person to be able to manipulate objects within that space. Based on that, this paper describes the current state-of-the-art in collaborative technologies with a critique of how well they support the required collaborative activities. Essentially, this paper suggests that, as of now, only through immersive Collaborative Virtual Environments (CVE) we are close to being able to achieve the seamless collaboration that exists in a face to face meeting.